Effect of MTAD on the shear bond strength of self-etch adhesives to dentin - Vajihesadat Mortazavi; Abbasali Khademi; Kazem Khosravi; Mohammadhossein Fathi; Mohammadesmaeil Ebrahimi-Chaharom; Shirin Shahnaseri; Navid Khalighinejad; Hamid Badrian (Wolters Kluwer Medknow Publications, 2012)
Background: As the use of different irrigants to eliminate residual debris and smear layer in the field of endodontic is unavoidable, by considering the effect of irrigants on the bond strength of resin composite restorations, this study was designed to evaluate the effect of a mixture of a tetracycline isomer, an acid, and a detergent (MTAD) on the shear bond strength of two self-etch adhesives, Clearfil SE Bond and Adper Prompt L- Pop to dentin. Materials and Methods: The crowns of 80 extracted premolars were transversally sectioned to expose dentin. Flat dentin surfaces were wet abraded with 320-grit abrasive paper and randomly assigned to eight groups according to two self-etch adhesive and four dentin surface treatments: direct application over smear layer (no treatment), etching with 35% phosphoric acid for 15s, 1 min 5.25% NaOCl/1 min MTAD and 20min 1.3% NaOCl/5min MTAD. Shear bond strength was tested 24 h after storage in distilled water at 37°C in incubator. Data were analyzed using one-way ANOVA followed by duncan post-hoc (α=0.05). Results: Phosphoric acid etching prior to SE Bond application significantly decreased the shear bond strength to dentin (P<0.05). Application of MTAD clinical protocol (20min 1.3% NaOCl/5min MTAD) did not significantly decrease the shear bond strength of self-etch adhesives to dentin (P=0.745) Conclusions: Based on the results of present investigation, it seems that the use of clinical protocol of 1.3% NaOCl as a root canal irrigant and a 5-min application of MTAD as a final rinse to remove the smear layer has no adverse effect on the shear bond strength of self-etch adhesives to dentin.